Service Evaluation on Automotive After-Sale Service - Nordin, N.; Yaacob, A. A.; Razak, R. C.; Radzi, W. N. W.; Saraih, U. N. (Journal of Advanced Research in Business and Management Studies, 2020)
After-sale service assumes a crucial part in reinforcing the bond between the association and clients. After-sales service refers to various processes which ensure customers are satisfied with the products and services of the organization. The needs and demands of the customers must be fulfilled for them to spread a positive word of mouth. In the present scenario, a positive word of mouth plays an important role in promoting brands and products. After sales service ensures products and services meet or surpass the expectations of the customers. After sales service include various activities such as steps and procedures to find out whether a particular customer is happy with the products or not. In this research, some of the variable is used to measure the after-sales service. The variable is including warranty, staff service, loyalty, safety and comfort level. The researcher will incorporate them to measure and observe how they influence the after-sale service.